EARLY DIAGNOSIS OF PURULENT FORMS OF ACUTE PYELONEPHRITIS - Qo’ziyev Sohib Saloyiddin o’g’li (KONFERENSIYALAR, 2025)
Аnnotation. This article provides an overview of one of the most relevant topics in modern urology – the early diagnosis of purulent forms of pyelonephritis. It presents the current state of the issue and highlights the key debatable aspects of the problem. The article reviews nearly all non-invasive imaging methods for diagnosing various forms of purulent pyelonephritis, demonstrating their capabilities, advantages, and limitations.